26.4k views
5 votes
–19y − 6y + 17y − –14 = –18

y=?

User Jkpieterse
by
4.9k points

2 Answers

2 votes

Answer:


y=(16)/(9)

Step-by-step explanation:

Given: –19y − 6y + 17y − –14 = –18

We have to isolate the variable (y) to get it by itself. Firstly, we'll get rid of the double negative.

–19y − 6y + 17y − –14 = –18

Subtracting a negative number by a negative number automatically means it's an addition sign.

–19y − 6y + 17y + 14 = –18

Now, let's add our common variables.

We have three.

–19y − 6y + 17y + 14 = –18

We get:

-18y + 14 = -18

The fourteen does not belong with the variable, so we'll move it to the other side. To do this, we'll subtract the fourteen on both sides of the equation.

-18y + 14 = -18

-14 -14

Now we have:

-18y = -32

The last step is to divide. In doing so, the quotient is:


y=(16)/(9)

User Havoc P
by
4.8k points
1 vote

Answer: y=4

Step-by-step explanation: first simplify the equation and then take off numbers equally from both sides

User Max Conway
by
4.3k points